Partial arytenoidectomy in 14 standing horses (2013–2017). Issue 4 (18th March 2019) - Gray, Sarah M.; Gutierrez‐Nibeyro, Santiago D.; Secor, Erica J.
Abstract: Objective: To report our experience with partial arytenoidectomy in sedated standing horses. Study design: Retrospective study. Animals: Fourteen client‐owned adult horses. Methods: The medical records (2013–2017) of horses treated with unilateral partial arytenoidectomy while standing and sedated were reviewed. Demographics, endoscopic findings, previous treatments, and outcome after surgery were investigated and recorded. Results: Thirteen horses had unilateral left‐sided recurrent laryngeal neuropathy (RLN) and 1 horse had bilateral RLN. Five horses had a previous failed prosthetic laryngoplasty. Left‐sided partial arytenoidectomy without mucosal closure was successfully completed in all horses under sedation and local anesthesia. Report of long‐term outcome was obtained via telephone conversations for 12 horses, of which 9 also had an endoscopic reevaluation performed; 3 horses had granulomas at the surgical site, of which 2 eventually required a permanent tracheostomy. Nine horses returned to athletic use without respiratory noise, 2 horses returned to athletic use with noise during exercise that was reduced compared with preoperative levels, and 1 horse continued to be used as a broodmare. Conclusion: Partial arytenoidectomy in standing horses was achieved with adequate sedation and local anesthesia. Clinical significance: Partial arytenoidectomy on standing sedated horses could be considered as an alternative to eliminate the risks associated with general anesthesia.